Climate change awareness among the livestock rearers of east coast of India - MAITI, SANJIT; JHA, SUJEET KUMAR; GARAI, SANCHITA; NAG, ARINDAM; BERA, A K; BHATTACHARYA, D; KALE, RAJIV B; DEB, S M (The Indian Journal of Animal Sciences, 2016)
The phenomenon of global climate change is directly affecting the livestock production system world overall. Therefore, understanding the changing climatic scenario by the millions of resource poor livestock rearers across the east coast of India found to be imperative to get information for strategic planning to improve the livelihoods of rural people. But, systematic methodology to assess climatic change awareness among the livestock rearers is currently not available. Therefore, a psychometric scale entitled “Climate Change Awareness Scale” was developed and applied among the randomly selected 480 livestock rearers of eastern coastal region of India. Results reflected majority of the population exhibit their strong level of awareness towards changing climatic scenario in general and particularly towards broad spectrum of climate change like causes, features, effects and impacts. It was also found that 37.188% of livestock rearers of coastal region were having higher level of awareness followed by 31.973% and 30.839% were having lower and medium level of awareness. Comparisons of state of awareness with the factual climatic data validated farmers’ claim and established the authenticity of the psychometric tool. Hence, this study will provide a significant tool for researchers and policy makers to assess state of climate change awareness among the end users and to develop appropriate adaptation strategies to minimize the risk of livestock sector to climate change.